Improve the micrologistic system of transportation sinter at metallurgical enterprises - Турпак, Сергій Миколайович; Грицай, Сергій Васильович; Віговська, Олена Олексіївна (Eastern-European Journal of Enterprise Technologies, 2011)
The transport system of sinter production is considered. The work of railway transportation at sinter plant is analyzed. The governance on the basis of logistic principles is proposed